Building evidence into youth health policy: a case study of the Access 3 knowledge translation forum - Daniel Waller; Fiona Robards; Carmen Huckel Schneider; Lena Sanci; Katharine Steinbeck; Sally Gibson; Tim Usherwood; Catherine Hawke; Stephen Jan; Marlene Kong; Melissa Kang (BMC, 2022)
Abstract Background Effective integration of evidence and youth perspectives into policy is crucial for supporting the future health and well-being of young people. The aim of this project was to translate evidence from the Access 3 project to support development of a new state policy on youth health and well-being within New South Wales (NSW), Australia. Ensuring the active contribution of young people within policy development was a key objective of the knowledge translation (KT) process. Methods The KT activity consisted of a 1-day facilitated forum with 64 purposively sampled stakeholders. Participants included eight young people, 14 policy-makers, 15 academics, 22 clinicians or managers from NSW health services, four general practitioners and one mental health service worker. Research to be translated came from the synthesized findings of the NSW Access 3 project. The design of the forum included stakeholder presentations and group workshops, guided by the 2003 Lavis et al. KT framework that was improved by the Grimshaw et al. KT framework in 2012. Members of the Access 3 research team took on the role of knowledge brokers throughout the KT process. Participant satisfaction with the workshop was evaluated using a brief self-report survey. Policy uptake was determined through examination of the subsequent NSW Youth Health Framework 2017-2024. Results A total of 25 policy recommendations were established through the workshop, and these were grouped into six themes that broadly aligned with the synthesized findings from the Access 3 project. The six policy themes were (1) technology solutions, (2) integrated care and investment to build capacity, (3) adolescent health checks, (4) workforce, (5) youth participation and (6) youth health indicators. Forum members were asked to vote on the importance of individual recommendations. These policy recommendations were subsequently presented to the NSW Ministry of Health, with some evidence of policy uptake identified. The majority of participants rated the forum positively. Conclusions The utilization of KT theories and active youth engagement led to the successful translation of research evidence and youth perspectives into NSW youth health policy. Future research should examine the implementation of policy arising from these KT efforts.